(untitled) (Dhaka University Journal of Applied Science and Engineering, 2024)
Wind energy is one of the most prevalent renewable sources nowadays, which has been projected to play an immense role in realizing the clean energy transition. This paper dives into one of the critical challenges in the grid integration of wind power plants, which is reactive power compensation. The static synchronous compensator (STATCOM) is commonly used to inject/absorb reactive power in wind power plants where the device is controlled with the traditional proportional-integral (PI) controller. This article investigates the effectiveness of the fuzzy logic controller (FLC) in managing the STATCOM to compensate and regulate the reactive power in a 9 MW grid-connected wind power plant. Due to its faster and malleable response, the FLC allows for greater flexibility in controlling the STATCOM. According to the findings, the voltage profile at the point of common coupling (PCC) is improved considerably in the case of the FLC compared to the PI controller, demonstrating the efficacy of the employed strategy. MATLAB-Simulink has been used to model and analyze the proposed system. We achieved a 6 percent improvement in voltage regulation when FLC was utilized instead of PI controllers. DUJASE Vol. 8 (1) 62-70, 2023 (January)